Karakteristik Diabetic Foot Ulcer (DFU) pada Individu dengan Diabetes Mellitus (DM): Studi Deskripsi – Cross Sectional - Kusumaningrum, Niken Safitri Dyan; Saputri, Afriana Dwi; Kusuma, Henni; Erawati, Meira (Journal of Holistic Nursing Science, 2020)
Diabetic Foot Ulcer (DFU) is one of the complications often experienced by patients with diabetes mellitus (DM). This is a serious problem that leads to disability, morbidity, and mortality among diabetic patients. However, in Indonesia, studies about DFU characteristics are very limited. This study aimed to describe DFU characteristics among patients with DM. A consecutive sampling involved patients who met inclusion criteria was performed in Tugurejo Hospital; Islamic Sultan Agung Hospital, and Dr. Moewardi Hospital. Their demographic characteristics, clinical condition, and wound appearances were noted and documented. Diabetic Foot Ulcer Assessment Scale (DFUAS) that consists of 11 characteristics was used to observe the wound features. The data were quantitatively analyzed to elucidate the result. A total of 73 patients participated in this study. It was revealed that 50.7% were females and 75.3% have been diagnosed with hyperglycemia. The average age of the respondents was 53.26 years. Observation of DFU characteristics showed that depth of wound was identified more in subcutaneous/ dermis to fatty tissue (40 patients; 54.8%) than in other layers. Moreover, our findings indicated that most of the respondents were identified at a severe level of the wound (55; 75.3%). It is concluded that DFU characteristics vary among patients with DM. Early identification and intensive surveillance are important to improve the management of DFU and to avoid lower limb amputation.